Sosialisiasi Pendidikan Hutan Sebagai Paru-Paru Dunia kepada Sekolah Dasar Negeri Pakal 1 Surabaya - Susi Hardjati; Sasiska Rani; Dinda Meryssa Bella; Istiqomah Mahmudah; Delvira Permata Sari; Selen Chaterine Valencia; Audrey Fairuz Herdiana (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
Forest is an ecosystem unit in the form of a stretch of land containing biological resources which are dominated by trees in communion with their environment, which cannot be separated from one another. Forests have many benefits for human life. These benefits can be seen in terms of ecology, hydraulics, economy, and health such as regulating forest climate, as the lungs of the world, preventing global warming, storing groundwater, and regulating water systems. In this case, socialization is carried out to elementary school students so that they can cultivate a caring attitude towards the forest from an early age. The socialization was held at SDN Pakal 1 Surabaya. The method used is the delivery of material through power points, the activities carried out include the delivery of material on the meaning of forests, how to conserve forests, and the consequences of not conserving forests. Socialization was also carried out in the form of audio- visual by showing short video clips about the importance of forests as the lungs of the world. This Community Service activity can be said to be successful because of the very good response and high enthusiasm from the students of SDN Pakal 1 Surabaya. Realizing the importance of this activity and the impact it can have in the future, it is hoped that this socialization activity can be continued to preserve forest sustainability starting at an early age.